GEOCHEMICAL AND FLOTATION STUDIES OF COPPER ORE OF NORTH WAZIRSTAN AGENCY (Biological Sciences - PJSIR, 2004)
Important copper deposits of North Wazirstan Agency are confined to Shinkai and Degan Paikhel areas Miran Shah Town. The copper mineralization in these areas is of native and sulphide types as veins, veinlets, stringers and rims around fragments and associated with cupriferous breecia. The cupriferous massive sulphides occur in basalts belonging to obducted ophiollite complex. An average copper contents of 17 ore samples is 0.45%. The flotation results show that maximum liberation of chalcopyrite with gangue minerals occurs at - 63 (240 mesh) size. The complex nature of valuable minerals with gangue does not hinder the separation of copper from the gangue materials. Results show that the copper contents of the ore were enhanced from 0.5% to 24.0% in the concentrate. For ensuring better results about grade and recoveries, further  studies on second and third stage flotation are needed.